The Effect Of Advertising Effectiveness On Buying Interest Through The Use Of Shopeepay E-Wallet - Nurhaliza, Aliyah; Lailla, Nor (UNIVERSITAS PAKUAN, 2025)
The development of information and communication technology has driven changes in consumer behavior, especially in digital payments through E-Wallets. ShopeePay, as one of the popular E-Wallets, offers ease and convenience in transactions. This study aims to analyze the effect of advertising effectiveness on consumer purchasing interest through the use of ShopeePay. The method used is quantitative descriptive with purposive sampling technique, involving 281 respondents who use ShopeePay in South Tangerang. Data were collected through online questionnaires and analyzed using SmartPLS 3.0. The results show that advertising effectiveness has a significant effect on purchasing interest, both directly and through the use of ShopeePay as a mediator. The use of ShopeePay itself has also been shown to significantly increase consumer purchasing interest. In conclusion, effective advertising can increase consumer purchasing interest by utilizing the convenience and benefits of using E-Wallets such as ShopeePay.